PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH TERHADAPPEMAHAMANKONSEP MATEMATISSISWAKELAS VIIISMPN 2 PANYABUNGAN KOTA KABUPATEN MANDAILING NATAL TAHUN PELAJARAN 2013/2014 - Nasution, Julayfah Irina; Anggraini, Villia; Harisman, Yulyanti (STKIP PGRI Sumbar, 2013)
This research was conducted based on the fact that the studentsâ understanding on mathematics concepts was still low and they were less active in the learning process. The aim of this research was to reveal the effect of using Make A Match cooperative learning model on the studentsâ activities, and to see whether the use of this model could improve the studentsâ understanding on mathematics concepts better than that of the conventional one in class VIII of SMPN 2 Panyabunagn Kota. This experimental research applied random design toward the subject. The population of the research was the students in class VIII of SMPN 2 Panyabungan Kota. The instruments used were observation sheet and a test which had been tested. The data then was analyzed by using one way t-test. The result of data analysis indicated that there was an improvement on the studentsâ activity in respective meeting. In addition, the result of hypothesis test showed that tcalculated > ttable, therefore, the hypothesis was accepted. In conclusion, the use of Make A Match cooperative learning model could improve the studentsâ understanding on mathematics concepts better than that of the conventional one in class VIII of SMPN 2 Panyabungan Kota.